Strategies and competences of nurses in men's health care: an integrative review - Josias Alves de Oliveira; Isabella Félix Meira Araújo; Gilberto Tadeu Reis da Silva; Anderson Reis de Sousa; Álvaro Pereira (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objectives: to synthesize scientific evidence on nurses' strategies and competencies in men's health care. Methods: an integrative review carried out in seven databases, with a time frame from 2009 to 2019, using the descriptors "men's health", "professional competence", "nursing", "nursing care" and "male" in Portuguese and in English. Results: ten articles were selected, in which it was demonstrated that nursing professionals develop their professional practices with regard to men's health care, in convergence with the general skills of the profession. The most used are health care; decision-making; Communication; administration; management; continuing education and leadership, consecutively. Final Considerations: professionals' efforts to strengthen health actions, aimed at male needs, in accordance with the general skills of the profession and the principles and guidelines of the Brazilian National Policy for Comprehensive Care to Men's Health.